Pharmaceutical supply chain models: A synthesis from a systems view of operations research - Ettore Settanni; Tomás Seosamh Harrington; Jagjit Singh Srai (Operations Research Perspectives, 2017)
This research evaluates reconfiguration opportunities in Pharmaceutical Supply Chains (PSC) resulting from technology interventions in manufacturing, and new, more patient-centric delivery models. A critical synthesis of the academic and practice literature is used to identify, conceptualise, analyse and categorise PSC models. From a theoretical perspective, a systems view of operations research is adopted to provide insights on a broader range of OR activities, from conceptual to mathematical modelling and model solving, up to implementation.
Keywords: 330; Supply networks; Modelling; Pharmaceuticals; Critical interpretative synthesis